1980
DOI: 10.1079/bjn19800006
|View full text |Cite
|
Sign up to set email alerts
|

Studies on copper and cobalt in dairy calves

Abstract: I. Studies on the effect of supplementing copper and cobalt were conducted in 4-to lo-month-old dairy calves during successive indoor and outdoor feeding periods on conserved forages and fresh pastures respectively. 4. Supplementation with Co alone had no effect on any of the measurements taken, but it had an additive effect on weight gains to Cu supplementation during the grazing period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Copper deficiency causes various disorders in animals such as anemia, retarded growth, immunological dysfunctions, reproductive disorders, and alter cardiovascular, nervous, and skeletal systems [1]. The effects of copper supplementation were reported in deficient dairy cows and calves using different levels and various form of copper with or without antagonists [8][9][10][11][12]. Similar studies were also performed in beef cattle [13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 68%
“…Copper deficiency causes various disorders in animals such as anemia, retarded growth, immunological dysfunctions, reproductive disorders, and alter cardiovascular, nervous, and skeletal systems [1]. The effects of copper supplementation were reported in deficient dairy cows and calves using different levels and various form of copper with or without antagonists [8][9][10][11][12]. Similar studies were also performed in beef cattle [13][14][15][16][17][18][19].…”
Section: Discussionmentioning
confidence: 68%
“…Some microbes can use Co to synthesize vitamin B 12 and other rumen microbial growth factors ( 52 ). Vitamin B 12 synthesis is necessary for many bacterial enzymes, and these enzymes participate propionic acid metabolism along with synthesis of methane, acetic acid, and methionine ( 3 , 53 ). Research using diets comprised mainly of wheat straw demonstrated that increasing Co inclusion rates significantly increase TVFA and acetic acid, propionic acid, and butyric acid production ( P < 0.05; 27).…”
Section: Resultsmentioning
confidence: 99%
“…Early studies showed that the supplementation of Co plus Cu had positive effects on microbial population, rumen fermentation and digestion of low quality forages in calves and heifers (Saxena and Ranjhan, 1980;Lopez-Guisa and Satter, 1992). Moreover, addition of Co and Cu had an additive effect on weight gains of dairy calves (Maro and Kategile, 1980). However, the effects of Co and Cu on vitamin B 12 synthesis and haematopoiesis in ruminants have not been reported.…”
Section: Introductionmentioning
confidence: 99%